(untitled) (International Journal of Built Environment and Sustainability, 2024)
Sustainable Development Goals (SDGs) represents the 2030 Agenda defined by the United Nations to attain sustainable development. It comprises outlines 17 goals that cover a range of issues. These goals focus on addressing the globe’s most crucial economic, communal, and environmental challenges to provide a more sustainable future for every individual. In India, the government has initiated several schemes and programmes for attaining the targets set for different SDGs, but addressing the complex challenges associated with sustainable development requires continued efforts and collaborations from multiple stakeholders including governments, individuals, public and private sectors. Achieving the SDGs is a continuous process, and some targets may need more time and effort to get achieved. Regular monitoring and evaluation are significant for tracking progress and addressing the gaps or challenges that may arise. The COVID-19 pandemic put a critical impact on the advancement towards attaining the targets set for all the SDGs globally. India has been found to be off track for 19 out of the 33 SDG indicators and there is an urgent need to accelerate the momentum of achieving the targets by 2030. AI presents significant opportunities to address these challenges in India. Overall, in India, Artificial Intelligence is seen as valuable tool to achieve the targets set for different goals in the coming years. In this paper, the authors have discussed the schemes and programmes initiated by the Government of India to attain these SDGs and the role of Artificial Intelligence in attaining the targets by the year 2030